International Knowledge Spillovers - Eugster, Johannes (IMF Working Papers; Working Paper ;, 2018)
How important is foreign knowledge for domestic innovation outcomes? How is this relation shaped by globalization and the attendant intensification of international competition? Our empirical approach extends the previous literature by analyzing a large panel comprising industries in both advanced and emerging economies over the past two decades. We find that barriers to the domestic diffusion of foreign knowledge have fallen significantly for emerging economies. For all countries, and especially for emerging economies, inflows of foreign knowledge have a growing and quantitatively important impact on domestic innovation. Controlling for the amount of domestic R and D, we find evidence that increases in international competitive pressure at the industry level had a positive effect on domestic innovation outcomes.